Transformación digital para el mejoramiento de la calidad de los servicios públicos en la unidad de avalúos y catastro en el gad quevedo, 2023 - Sanchez Anchundia, Xiomara Tahis (2025)
In this research, it was analyzed how digital transformation influences the improvement of the quality of public services in the Appraisal and Cadastre Unit in the Decentralized Autonomous Government of Quevedo. The problem focuses on resistance to change on the part of officials, delay in response times to users and deficiency in implementing digital tools. Therefore, it is essential to establish improvements for the quality of public services through digitalization, being a key element that contributes to efficient and transparent management in public management. For the analysis of the use of the digital transformation of the Appraisals and Cadastre Unit in the GAD of Quevedo, data collection techniques were used to improve the quality of the public services offered to users. Descriptive, exploratory and field research was applied to know the current situation of the unit with respect to the digital tools they use. Therefore, a sample study was carried out on 295 people, where an interview was conducted with the director of the unit, also with 20 officials and finally with 274 users to know the perception and satisfaction of users in relation to the use of digital transformation and the quality of public services. The results obtained from the research led to the conclusion that there are several challenges in the use of digital transformation, but significant opportunities for improving the quality of public services.